Thermal in situ TEM experiment on nanoscale indium islands - Qiu, Ren (My University, 2017)
One of the limitations of transmission electron microscopy are the beam damaging effects that can arise from interactions between the primary high energy electron beam and the sample. The effects include radiolysis of organic and polymer materials, knock-on and sputtering damages, and beam heating induced by phonon excitation from inelastic scattering of incident electrons. In this master thesis project, an experimental study of the local beam heating effect is carried out using electron thermal microscopy technique based on transmission electron microscope (TEM) dark field imaging. In situ heating experiments with different beam settings in the TEM are performed on nanoscale indium islands deposited on top of 50 nm thick silicon nitride membrane through metal evaporation. The specimen is heated by a TEM heating holder and the amount of beam heating is quantified by evaluating the change in melting point of the indium island. For easier data analysis, image processing is done to identify the indium islands in the bright and dark field images. First, OTSU thresholding and Watershed algorithm are used on the bright field image to recognize the indium islands. Dark field images are then rigidly aligned with respect to the bright field image so that all indium islands are identified through the whole melting process. The melting temperature of each indium island of interest is then determined from the change in contrast in the dark field image at the transition temperature from solid to liquid state. The acceleration voltage, the illumination area and the beam current are the three main parameters of the incident electron beam influencing the amount of induced beam heating in a sample. Effect of the acceleration voltage at 120 and 200 kV is compared. The electron beam illuminating area on the sample is estimated using a standard TEM grating sample. The beam currents are measured using the TEM fluorescent screen, which is independently calibrated as part of this work. A custom made Faraday cup is produced on a gold tip using a focused ion beam (FIB). The Faraday cup is mounted in a Nanofactory holder and the beam current is measured with a picoammeter. The calibrated conversion coefficient for the beam current is then determined by comparing the current values measured by the Faraday cup and the fluorescence screen. The melting temperature of the indium islands is used as a reference point to quantify the heating effect of the electron beam. The beam heating is investigated as a function of electron beam current and acceleration voltage by measuring the change of the indium island melting temperature registered on the external heating control unit. Based on the observations, a method to quantify the local electron beam heating in TEM is proposed. This is important for quantitative data evaluation of in situ thermal TEM experiments.
Keywords: Fysik; Physical Sciences